Plants' Impact on the Human Brain-Exploring the Neuroprotective and Neurotoxic Potential of Plants - Georgiana Moise; Alex-Robert Jîjie; Elena-Alina Moacă; Iasmina-Alexandra Predescu; Cristina Adriana Dehelean; Alina Hegheș; Daliborca Cristina Vlad; Roxana Popescu; Cristian Sebastian Vlad (MDPI AG, 2024)
Background: Plants have long been recognized for their potential to influence neurological health, with both neuroprotective and neurotoxic properties. This review explores the dual nature of plant-derived compounds and their impact on the human brain. Discussion: Numerous studies have highlighted the neuroprotective effects of various phytoconstituents, such as those found in Ginkgo biloba, Centella asiatica, Panax ginseng, Withania somnifera, and Curcuma longa. The neuroprotective compounds have demonstrated antioxidant, anti-inflammatory, and cognitive-enhancing properties, making them promising candidates for combating neurodegenerative diseases and improving brain function. Polyphenolic compounds, triterpenic acids, and specific phytocompounds like the ones from EGb 761 extract have shown interactions with key enzymes and receptors in the brain, leading to neuroprotective outcomes. However, this review also acknowledges the neurotoxic potential of certain plants, such as the Veratrum species, which contains steroidal alkaloids that can cause DNA damage and disrupt neurological function, or Atropa belladonna, which interfere with the normal functioning of the cholinergic system in the body, leading to a range of symptoms associated with anticholinergic toxicity. Conslusions: This review also emphasizes the need for further research to elucidate the complex mechanisms underlying the neuroprotective and neurotoxic effects of plant-derived compounds, as well as to identify novel phytoconstituents with therapeutic potential. Understanding the complex relationship between plants and the human brain is crucial for harnessing the benefits of neuroprotective compounds while mitigating the risks associated with neurotoxic substances. This review provides a comprehensive overview of the knowledge on the neurological properties of plants and highlights the importance of continued research in this field for the development of novel therapeutic strategies targeting brain health and neurological disorders.